Smallholder dairy systems in the Kenya highlands: breed preferences and breeding practices - Bebe, B.O.; Udo, H.M.J.; Rowlands, G.J.; Thorpe, W.R. (Elsevier, 2003)
A stratified random sample, cross-sectional survey of 1755 households in the Kenya highlands was conducted between June 1996 and April 1998 to evaluate the rationale underlying smallholders’ breeding decisions. Additional data were collected in a follow-up survey of 50 households sub-sampled from the main survey sample. Cattle-keeping households were 987, of which 62% kept Friesian (FR) and Ayrshire (AY), 22% kept East African Zebu, Boran and Sahiwal (ZB) cattle and 16% kept Guernsey and Jersey (GJ) breeds. Farmers keeping ZB and GJ ranked producing milk for family consumption the most important reason for keeping cattle, whereas those keeping FR and AY ranked producing milk for cash income most highly. Farmers’ relative preference for GJ, AY and FR for high milk yield over hardiness was respectively 3.46, 7.58 and 17.63 times more when compared with preference for ZB. Additional attributes rated highly in the Bos taurus breeds were high butterfat yields, heavier bodyweight, unselective feeding behaviour in zero-grazing systems, hardiness and disease resistance in semi-zero- and free-grazing systems and high market value. Breeding practices tended to favour the use of dairy breeds of larger body size, particularly Friesian, which is inconsistent with technical recommendations that favour the use of the smaller dairy cattle breeds. These findings suggest that multiple objectives, including the need for more milk, adaptability to local feed conditions and diseases, and the provision of non-market production such as manure, insurance and financing roles of cattle, underlie smallholders’ breeding decisions in the Kenya highlands.